Organizational Justice and Employee Retention: A Theoretical Framework for Malaysian and Indonesian Higher Learning Institutions - Harun, Shariff; Choirisa, Septi Fahmi; Rizkalla, Nosica (Information Management and Business Review, 2023)
Employee retention has emerged as a pressing concern within knowledge-based organizations due to the non-substitutability of individual abilities and their substantial influence on organizational achievements. Therefore, the retention of proficient staff is a crucial strategic approach, particularly for Malaysian and Indonesian Higher Learning Institutions (HLIs). Thus, this study seeks to understand the antecedents that could influence HLIs’ workforce retention. To achieve the objective, a content analysis approach is used to discover potential antecedents of fairness that affect HLIs’ workforce retention. The Organizational Justice Theory is then employed as the theoretical foundation to examine and synthesize the antecedents. Three antecedents are addressed during the examination and discussion: distributive justice, procedural justice, and interactional justice. Through this, three organizational justice propositions are offered, and the framework developed in this conceptual study highlights the retention practices and instigators. This study’s conceptual nature provides preliminary insights into the employees’ retention experience in the Malaysian and Indonesian HLI context. This study contributes to the body of knowledge by illuminating the antecedents that promote employee retention, resulting in a practical framework that can be used by the HLIs to formulate strategies and policies to reduce the financial and business risk due to the high employee attrition rate. Subsequently, achieving the United Nations Sustainable Development Goals of good health and well-being (Goal 3) and quality education (Goal 4).